Nanotechnology-Enabled Antibiotic Therapy: The Promise of Transfersomal Tigecycline in Combating Methicillin-Resistant Staphylococcus aureus - Khasawneh, Dyala M.; Oweis, Rami J. (Current Drug Delivery, 2025)
<span class=
Keywords: methicillin-resistant Staphylococcus aureus (MRSA)